Nitinol manufacturing and micromachining: A review of processes and their suitability in processing medical-grade nitinol. (February 2019) - Mwangi, James Wamai; Nguyen, Linh T.; Bui, Viet D.; Berger, Thomas; Zeidler, Henning; Schubert, Andreas
Abstract: An increase in geriatric population coupled by a growing incidence of different vascular ailments including peripheral vascular and coronary artery diseases imply that the medical devices market will continue to enlarge. As demand for minimally invasive surgical procedures and treatments increase, so does the significance of the abilities of nitinol, including shape memory, superelasticity, high fatigue resistance, corrosion resistance and biocompatibility which have revolutionized the medical device manufacturing sector. In order to fully exploit the capabilities of nitinol, sound and application oriented machining processes have to be selected for optimum efficiency. This is especially so for nitinol since it is a hard material to machine owing to its phase transformation and work hardening. Though stand alone research on processing nitinol is available, vital comparison information regarding to strengths and limitations of different machining processes applied in micromachining nitinol is lacking. This study presents on steps in a nitinol processing chain and offers a juxtaposition between different nitinol manufacturing, forming, machining and post processing methods including pointing out how they may affect final part performance. Different performance measurement parameters have been used to categorize the processes and a suitability analysis has been made which can offer a guide on when to use which method.